2020 IEEE International Conference on Communications Workshops (ICC Workshops) 2020
DOI: 10.1109/iccworkshops49005.2020.9145107
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of UK's Cellular Network for Vehicle to Grid Energy Trading: Opportunities for 5G and Beyond

Abstract: The proliferation of plug-in electric vehicles (PEV) and advances in high-speed low latency communication networks redefine the relationships between electricity providers and endusers. A group of PEV owners, coordinated by an aggregator, can participate in ancillary energy markets to stabilize electricity grids and, in return, receive payments for services rendered. However, PEVs are typically parked across a dispersed region possibly with diverse signal strength and data rates. Vehicleto-Grid (V2G) applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…A substantial part of the latency can be attributable to the 4G link in this calculation. It was observed in our earlier work [27,29] that the Wi-Fi link latency can constitute up to 50 ms of the total latency value. However, the number of PEVs connected to the Wi-Fi access point has a significant impact on this figure.…”
Section: Experimental Results and Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…A substantial part of the latency can be attributable to the 4G link in this calculation. It was observed in our earlier work [27,29] that the Wi-Fi link latency can constitute up to 50 ms of the total latency value. However, the number of PEVs connected to the Wi-Fi access point has a significant impact on this figure.…”
Section: Experimental Results and Analysismentioning
confidence: 88%
“…In our preliminary work [27], we developed a V2G test bed for a charging station to test the performance of the proposed communication infrastructure. The communication infrastructure included a Wi-Fi link within the charging station between PEVs and an EVSE, a 4G cellular network between the EVSE and the base station, and fiber optic internet between the base station and grid's control room.…”
Section: Introductionmentioning
confidence: 99%
“…In this research work, we have compared wireless last-mile communication technologies as shown in Table 7 , based on estimated latency and data rate values that can be found from the literature and previous research work [ 23 , 25 ]. According to the references [ 23 , 26 , 27 ] MCL (signal strength) can impact significantly on the value of the latency. The latency for two standard protocols—the transmission control protocol (TCP) and user datagram protocol (UDP)—have been simulated for a smart grid IoT network in [ 28 ].…”
Section: Testbed Resultsmentioning
confidence: 99%
“…In recent years, the participation of plug-in electrical vehicle (PEV) batteries in the ancillary services market, also known as V2G, has gained popularity as the use of PEVs enhance system efficiency, while providing monetary benefits to PEV owners [5]. In a V2G application, each PEV battery is charged and discharged within a time window according to real-time automatic generation control signals [17]. Regarding wireless networks such as 3G and 4G, the latency assessment has been compared in [19], which reports an average latency value of 35 ms for 4G and a latency of 45 ms for 3G.…”
Section: Different Smart Grid Applicationsmentioning
confidence: 99%